Development of a Fast and Sensitive UPLC–MS/MS Analytical Methodology for Fenebrutinib Estimation in Human Liver Microsomes: In Vitro and In Silico Metabolic Stability Evaluation - Mohamed W. Attwa; Aishah M. Alsibaee; Haya I. Aljohar; Ali S. Abdelhameed; Adnan A. Kadi (Separations, 2023)
Fenebrutinib (GDC-0853; FNB) is an oral small molecule that was developed by Roche Pharmaceuticals to slow multiple sclerosis progression. FNB is a reversible bruton tyrosine kinase (BTK) inhibitor, which showed the maximum potency of BTK inhibitors in phase III clinical trials for multiple sclerosis. In the current study, a fast, specific, and sensitive UPLC-MS/MS method for FNB quantification in human liver microsomes (HLMs) was established with application to the evaluation of metabolic stability. The UPLC-MS/MS methodology was verified using the stated USFDA validation guidelines for bioanalytical methodologies that involve selectivity, linearity, accuracy and precision, carryover and extraction recovery, stability, and matrix effect. The FNB calibration curve displayed a linearity in the range from 1 ng/mL to 3000 ng/mL (y = 1.731x + 2.013; R2: 0.9954; RSD < 4.37%) in the HLMs matrix. The limit of quantification was 0.88 ng/mL, which verified the UPLC-MS/MS analytical method sensitivity. The intraday and interday precision and accuracy results of the developed UPLC-MS/MS method were −3.99–14.0% and 0.52–3.83%, respectively. FNB and savolitinib (SVB) (internal standard) were chromatographically separated utilizing an isocratic mobile phase system with a ZORBAX Eclipse plus-C18 (50 mm, 2.1 mm, and 1.8 μm) column. The metabolic stability parameters for FNB, involving high intrinsic clearance (58.21 mL/min/kg) and a short in vitro half-life (13.93 min), revealed the high extraction ratio of FNB. Reviewing the literature revealed that the current UPLC-MS/MS method is the first analytical method for FNB quantification in the HLMs matrix with application to the assessment of FNB metabolic stability.